Pengaruh Sample Size terhadap Kestabilan Item Parameter Estimate pada Item Response Theory Model Tiga Parameter Logistik - Samritin Samritin (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2017)
This study aims to determine the stability of the parameter estimates of the test items on the modern test theory (IRT) for the three-parameter logistics model (3PL). This study uses a simulation method. Simulation data was generated using the WinGen for Windows program. Estimation stability analysis was carried out using the correlation between true parameters with estimate parameters and RMSE. The results showed that for sample sizes 500, 750, and 1000, the correlation coefficient (ρ) was 0.901, 0.988, and 0.992 respectively with RMSE 0.901, 0.351, and 0.273 for the difficulty parameter (b), correlation coefficient (ρ) of 0.746, 0.807, and 0.830 with an RMSE of 0.746, 0.304, and 0.281 for the power of difference parameter (a), the correlation coefficient (ρ) of 0.642, 0.667, and 0.679 with an RMSE of 0.642, 0.057, and 0.056 for the pseudo-guessing parameter. Based on the results of data analysis it was concluded that the larger the sample size, the more stable the item parameter estimates